KEBIJAKAN AFIRMATIF DALAM PENGENTASAN DAERAH TERTINGGAL DI PROVINSI NUSA TENGGARA TIMUR - Toda, Hendrik; Umbu Eda, Roynaldo Oktorian (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2020)
In accelerating the development of a number of disadvantaged areas, as a form of affirmative action, strategic steps are needed. This study aims to see how the form of affirmative policy in the alleviation of disadvantaged areas in NTT. This type of research used in this study is the study of literature as a collection technique, data by studying books, literature, notes, and reports that have to do with the problem of inequality and underdeveloped development in NTT. The results of the literature study indicate that the province of East Nusa Tenggara is ranked second after Papua, as a disadvantaged area. This is based on the level of the human development index (HDI) in NTT which is still below the national HDI standard and the low literacy rate in NTT. Affirmative Action as an effort to reduce regional disparity by the Central Government and the NTT Government is one of the national priorities and has a very important role. However, in its implementation, there is still a difference between the Central Government program and the character and needs of the region in NTT and a fairly long range of controls that results in the implementation of affirmative actions that are less effective in dealing with backwardness in NTT. Keywords: Affirmative, Lagging Regions, Gaps.